2014
DOI: 10.1186/2008-2231-22-42
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase activity modulation by some street drug: molecular docking simulation and experimental investigation

Abstract: BackgroundAdenosine deaminase (ADA) is an enzyme that plays important roles in proliferation, maturation, function and development of the immune system. ADA activity may be altered by variety of substances including synthetic or natural products. Morphine, cocaine and their analogs exert immune suppressive activities by decreasing immune system function. The purpose of this study is to confirm that this possible effect may be modulated by interaction of these substances with ADA activity by experimental and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…By contrast, ibuprofen and medazepam effects on immune deficiency have been reported. This revealed that purine compound may act as ADA activator [31]. Thus, ADA, being a single chain protein, performs more than one function, consistent with the definition of a moonlighting protein.…”
Section: Adenosine Deaminasesupporting
confidence: 69%
See 1 more Smart Citation
“…By contrast, ibuprofen and medazepam effects on immune deficiency have been reported. This revealed that purine compound may act as ADA activator [31]. Thus, ADA, being a single chain protein, performs more than one function, consistent with the definition of a moonlighting protein.…”
Section: Adenosine Deaminasesupporting
confidence: 69%
“…Moreover, ADA activity changes in a variety of other diseases including acquired immunodeficiency syndrome (AIDS), anemia, various lymphomas, tuberculosis, and leukemia. On the other hand, ADA regulates the levels of endogenous adenosine which results in immune system suppression by inhibiting lymphoid or myeloid cells, including neutrophils, macrophages, lymphocytes and platelets [31].…”
Section: Adenosine Deaminasementioning
confidence: 99%
“…Doravirine is not expected to be a perpetrator of drug–drug interactions against islatravir. The effect of doravirine on the adenosine deaminase metabolic pathway is unknown, but very few drugs are known to affect this pathway [ 26 , 27 ]. To evaluate the potential of islatravir and doravirine as a combination HIV-1 treatment regimen, it is important to characterize the pharmacokinetics and safety profile when coadministered.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is also associated with renal vasoconstriction, which causes the retention of uric acid (47). In patients receiving diuretics and antihypertensive agents for the treatment of hypertension, it was reported that the levels of uric acid increased and hyperuricemia increased to a rate of 58% (48). High uric acid levels reduce renal blood flow and GFR (49).…”
Section: Hyperuricemia and Hypertensionmentioning
confidence: 99%